Iodine biofortification of wheat, rice and maize through fertilizer strategy - Cakmak I. (2017)
© 2017 Springer International Publishing Switzerland Aim: Iodine (I) deficiency is distinct from other micronutrient deficiencies in human populations in having a high endemic prevalence both in well-developed and in developing countries. The very low concentration of iodine in agricultural soils and cereal-based foods is widely believed to be the main reason of iodine deficiency in humans, especially in developing countries. In the present study, the possibility of using iodine containing fertilizers for agronomic biofortification of cereal grains with iodine was studied. The aim was to establish the best application method (to the soil or as foliar spray), the best form of iodine (potassium iodate or potassium iodide) and the optimal dose of iodine. Additionally, experiments were conducted to study transport of iodine in plants and localization of iodine within the grains. Materials and methods: Experiments were conducted both under greenhouse conditions and in the field on wheat (Triticum aestivum) grown in Turkey and Pakistan, on rice (Oryza sativa) grown in Brazil, Thailand and Turkey and on maize (Zea mays) grown in Turkey. The iodine concentration in the grain, localization of iodine in different grain fractions of wheat (i.e., endosperm, bran and embryo) and iodine concentration of both brown rice and polished rice was analyzed. In short-term experiments, the translocation of iodine from older into younger leaves was also studied. Inductively coupled plasma mass spectrometry (ICP-MS) was used for analysis of iodine in plant and soil samples. Results: In greenhouse experiments on wheat, soil-applied potassium iodide (KI) and potassium iodate (KIO 3 ) at increasing rates (i.e., 0, 0.1, 0.25, 1, 2.5, 5, 10 and 20 mg I kg −1 soil) both iodine forms substantially increased iodine concentration in the shoot, with the highest shoot iodine resulting from the KI treatments. However, these soil treatments did not affect iodine concentrations in the wheat grain, with the exception of the highest iodine rates (i. e., 10 and 20 mg I kg −1 soil) which also depressed the grain yield. In contrast to the soil applications, foliar spray of KI and KIO 3 at increasing rates during heading and early milk stages did enhance grain iodine concentrations up to 5- to 10-fold without affecting grain yield. Including KNO 3 or a surfactant to the iodine containing foliar spray further increased the grain iodine concentration. In a short-term experiment using young wheat plants, it was found that iodine is translocated from older into younger leaves after immersion of the older leaves in solutions containing KI or KIO 3 . Adding KNO 3 or a surfactant in the immersion solution also promoted leaf absorption and translocation of iodine into younger leaves. Field experiments conducted in different countries confirmed that foliar application with increasing rates of iodine significantly increased grain iodine concentrations in wheat, brown rice and maize. This increase was also found in the iodine concentration of the endosperm part of wheat grains and in polished rice. Conclusions: The results of the present study clearly show that foliar application of iodine containing fertilizers is highly effective in increasing grain iodine concentrations in wheat, rice and maize. Presented results suggest that iodine is translocated from shoot to grain by transport in the phloem. Spraying KIO 3 up to the rate of 0.05% w/v is suggested as the optimal form and rate to be used in agronomic biofortification with iodine. The substantial increase in grain iodine concentrations could contribute to the prevention of iodine deficiency in human populations with low dietary iodine intake. The reasons behind the higher effectiveness of foliar-applications compared to the soil applications of iodine fertilizers in improving grain iodine concentration are discussed.